2013
DOI: 10.1177/0363546513497566
|View full text |Cite
|
Sign up to set email alerts
|

Autograft Versus Nonirradiated Allograft Tissue for Anterior Cruciate Ligament Reconstruction

Abstract: Background An autograft has traditionally been the gold standard for anterior cruciate ligament reconstruction (ACLR), but the use of allograft tissue has increased in recent years. While numerous studies have demonstrated that irradiated allografts are associated with increased failure rates, some report excellent results after ACLR with nonirradiated allografts. The purpose of this systematic review was to determine whether the use of nonirradiated allograft tissue is associated with poorer outcomes when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 41 publications
2
106
0
Order By: Relevance
“…Driven by results of ACLT models, current clinical practice includes repair of the torn ACL in an effort to arrest or slow the development of OA following a traumatic event that tears the ACL. Reconstruction of the ACL is usually accomplished by the use of either autograft or allograft tissue [12]. Unfortunately, surgical reconstruction of the injured joint does not appear to prevent PTOA.…”
Section: Introductionmentioning
confidence: 99%
“…Driven by results of ACLT models, current clinical practice includes repair of the torn ACL in an effort to arrest or slow the development of OA following a traumatic event that tears the ACL. Reconstruction of the ACL is usually accomplished by the use of either autograft or allograft tissue [12]. Unfortunately, surgical reconstruction of the injured joint does not appear to prevent PTOA.…”
Section: Introductionmentioning
confidence: 99%
“…However, two meta-analyses comparing the two main graft types (BPTB vs. ST) have demonstrated that a SSD superior to 3 mm was less frequent in BTPB compared to ST grafts [95,96]. Regarding the use of allografts, some authors reported similar outcomes compared to autografts [97,98], while others suggested that they may be inferior [99]. As for the double-bundle HS autograft technique, there are indications suggesting that it may be superior in terms of sagittal and rotational laxity [100][101][102].…”
Section: Knee Laxity After Anterior Cruciate Ligament Reconstructionmentioning
confidence: 99%
“…the ideal graft should have rapid incorporation, low failure rates, a high degree of safety, low donor site morbidity, wide availability, and low cost. [13,14] Unfortunately no such graft exists. By now there is no affirmative data about the difference between autograft and allograft reconstruction for ACL tears.…”
Section: Discussionmentioning
confidence: 99%